A study on effect of inspiratory muscle training in upper abdominal surgery patients - MAYURA P.DESHMUKH; G.D.VISHNU VARDHAN; DR.TUSHAR J. PALEKAR (International Journal of Pharma and Bio Sciences, 2017)
To investigate the effect of the Inspiratory Muscle Training in improving the maximum inspiratory pressure (PImax) in upper abdominal surgery patients, 30 patients were selected by convenient sampling method, devided into two groups. PImax of both the groups was measured thrice throughout the treatment protocol. Experimental Group received treatment with IMT threshold device, followed by thoracic expansion exercises emphasizing on the basal expansion exercises. Conventional Group received only the thoracic expansion exercises. IMT device increases the inspiratory muscle strength post operatively. Comparing the values of PImax in both the groups. IMT given by threshold device associated with the thoracic expansion exercises will improve the PImax in upper abdominal surgery patients.